2013
DOI: 10.1371/journal.pone.0080044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GA3 Treatment on Seed Development and Seed-Related Gene Expression in Grape

Abstract: BackgroundThe phytohormone gibberellic acid (GA3) is widely used in the table grape industry to induce seedlessness in seeded varieties. However, there is a paucity of information concerning the mechanisms by which GAs induce seedlessness in grapes.Methodology/Principal FindingsIn an effort to systematically analyze the cause of this GA3-induced seed abortion, we conducted an in depth characterization of two seeded grape cultivars (‘Kyoho’ and ‘Red Globe’), along with a seedless cultivar (‘Thompson Seedless’),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…In grapevine, the effects of GA application on berry enlargement, the induction of seedlessness in seeded cultivars and ripening have been the subject of study for quite some time [17,19,37-39]. Interestingly, we have previously demonstrated that the exogenous pre-bloom application of GA 3 inhibited berry growth in seeded ‘Kyoho’ and ‘Red Globe’ cultivars, yet stimulated berry growth in ‘Thompson Seedless’ [17]. Similarly, it has also been shown that berry growth was inhibited in the seeded grape cultivar ‘Emperador’ and promoted in the seedless cultivar ‘Emperatriz’ upon GA 3 application [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In grapevine, the effects of GA application on berry enlargement, the induction of seedlessness in seeded cultivars and ripening have been the subject of study for quite some time [17,19,37-39]. Interestingly, we have previously demonstrated that the exogenous pre-bloom application of GA 3 inhibited berry growth in seeded ‘Kyoho’ and ‘Red Globe’ cultivars, yet stimulated berry growth in ‘Thompson Seedless’ [17]. Similarly, it has also been shown that berry growth was inhibited in the seeded grape cultivar ‘Emperador’ and promoted in the seedless cultivar ‘Emperatriz’ upon GA 3 application [22].…”
Section: Discussionmentioning
confidence: 99%
“…The exogenous pre-bloom application of gibberellic acid (GA 3 ) to grapevine, which is an economically important crop that has long been an important component of the human diet, is commonly used to induce seedlessness [17,18], establish early ripening [19], and enhance berry size in seedless cultivars [20-22]. However, despite its importance in viticulture, the precise mechanism by which GA elicits these complex outcomes remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [34, 58] have reported that seed weight of seedless grapes usually begin to decrease at 27 ~ 33 days after full bloom (DAF), and so seeds from 9 seedless and 9 seeded grape progeny were collected at 24, 27, 30, 33, 36, 39 and 42 DAF (Additional file 11: Figure S5). Fruits of all progeny individuals were slashed with scalpel, and then seeds were immediately picked out without damage using tweezers and put into centrifuge tubes which were already soaked in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The GA3 -induced increase in cell damage may be caused by reactive oxygen species, a decrease in antioxidant enzymatic activities, and an alteration of the expression of genes related to seed development (Cheng et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellic acid (GA3) is widely used to induce seedlessness in seeded varieties in grapes (Fukunaga & Kurooka, 1988, Ogasawara, 1985, Ogasawara and Hirata, 1985, Fellman et al, 1991, Shiba, 1980, Kazunori et al, 2001and Cheng et al, 2013, cherry (Beppu et al, 2001 and, loquat (Mesejo et al, 2010) and other fruits (Pharis and King, 1985).…”
Section: Introductionmentioning
confidence: 99%